A sense of connectedness, transcendent experiences, and insights for compassionate action emerge through an international collective labyrinth walk with a shared intention during the COVID-19 pandemic - McGee, Jocelyn Shealy; Katzenmeyer, Christine; Boddie, Stephanie Clintonia; Meraz, Rebecca; Wood, Sinai (Frontiers in Psychology, 2023)
Labyrinth walking is an integrative contemplative practice that aims to engage the body, mind, heart, mind, and spirit. In this article, qualitative findings from the first year of a mixed methods study on collective labyrinth walking with a shared intention are described. This form of labyrinth walking is distinct in that it involves a shared social experience, either locally or non-locally, in which practitioners walk at the same time in solidarity for the same reason. The study is unique in that it took place at the height of the COVID-19 pandemic which was a time in recent history that evoked fear, uncertainty, grief, isolation, and disconnectedness for many persons around the world. The sample was comprised of 461 participants from 19 countries who participated in a collective labyrinth walk with a shared intention on World Labyrinth Day 2021. Most participants were women in middle to later life from the United States. Data was collected through an anonymous online survey and analyzed using the qualitative methodology of Interpretive Phenomenological Analysis. Three predominant themes emerged from practitioners’ narrative accounts of their lived experiences: 1) a sense of connectedness (i.e., intrapersonal, interpersonal, transpersonal, labyrinth) was cultivated through collective labyrinth walking with a shared intention; 2) practitioners reported qualities associated with “transcendent” experiences during this experience (i.e., boundlessness, ultimacy, transcendence, positive emotions); and 3) practitioners had insights for compassionate action. Findings suggest that collective labyrinth walking with a shared intention can contribute to individual and group flourishing during times of distress. Quasi-experimental and experimental research designs are needed to build on this exploratory developmental research and are described in this article.